Advances in explainable AI applications for smart cities - Ghonge, Mangesh; Pradeep,Nijalingappa; Jhanjhi,Noor Zaman; Kulkarni,M Praveen (Hershey, PA : Engineering Science Reference, 2023)
'This book is an essential resource for undergraduate and postgraduate students, researchers, academicians, industry professionals, and scientists working in research laboratories. It provides a comprehensive overview of XAI concepts, advantages over AI, and its applications in smart city development. By showcasing the impact of XAI on various smart city applications, the book enables readers to understand the importance of XAI in creating more sustainable and efficient smart cities. Additionally, the book addresses the open challenges and research issues related to XAI in modern smart cities, providing a roadmap for future research in this field. Overall, this book is a valuable resource for anyone interested in understanding the importance of XAI in smart city applications'--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Smart cities; Artificial intelligence; Human-computer interaction